Distance learning for elementary school students: case study in Saudi Arabia - Munshi, Asmaa; Aljojo, Nahla (International Journal of Engineering and Technology, 2018)
This study mainly focuses on distance learning for elementary schools in Saudi Arabia and how best to apply it. This involves designing and implementing a website similar to any Learning Management System; however, this system will focus only on elementary school students. Distance learning is rarely applied globally in elementary schools and has not yet been introduced in Saudi Arabian elementary schools. Although it is applied in some Saudi Arabian universities, the systems or applications used in distance learning can prove slightly problematic for use by younger pupils, such as elementary students. The data were collected through inexpensive means using a paper-based questionnaire. The population for this study was 170 participants including elementary school students and teachers of both genders. The data collected for this study supports two goals. The first goal is to get the students’ opinions about whether they would like to take online classes, and the second seeks their feedback if they have already taken any previous online classes. Questionnaires were distributed in an offline environment by gathering the data from the schools. The preliminary analysis reveals that there is a need and desire from both students and teachers for distance learning, especially online classes in elementary schools.